2022
DOI: 10.3389/fbioe.2022.914979
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid Particle-Flow CFD Modeling Approach in Truncated Hepatic Arterial Trees for Liver Radioembolization: A Patient-specific Case Study

Abstract: Hepatocellular carcinoma (HCC) is the most common form of primary liver cancer. At its intermediate, unresectable stage, HCC is typically treated by local injection of embolizing microspheres in the hepatic arteries to selectively damage tumor tissue. Interestingly, computational fluid dynamics (CFD) has been applied increasingly to elucidate the impact of clinically variable parameters, such as injection location, on the downstream particle distribution. This study aims to reduce the computational cost of suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Bomberna et al. ( 2022 ) also investigated the effect of truncating the geometry to reduce computational effort. They found that modeling only the larger branches and assuming particles follow flow distributions in some of the smaller branches could lead to up to 27% less computational effort while outlet-specific differences in particle distributions deviated at most 3.5%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bomberna et al. ( 2022 ) also investigated the effect of truncating the geometry to reduce computational effort. They found that modeling only the larger branches and assuming particles follow flow distributions in some of the smaller branches could lead to up to 27% less computational effort while outlet-specific differences in particle distributions deviated at most 3.5%.…”
Section: Resultsmentioning
confidence: 99%
“…(Lertxundi et al., 2021 ) and Bomberna et al. ( 2022 ) showed that judicious removal of certain parts of the geometry has only a small effect on the simulated microsphere distributions. This supports CFD as a relevant tool in the clinic, where the large computational resources required for detailed simulations are often unavailable.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, 3D computational fluid dynamics simulations have been made for liver radioembolization, which makes use of catheters to deploy radiation‐emitting microspheres to desired locations in the hepatic artery network (Aramburu et al, 2019, 2020; Bomberna et al, 2022; Taebi et al, 2020). Important parameters such as the size, injection velocity of microspheres, and the location of catheter tip were investigated (Aramburu et al, 2020).…”
Section: Hepatic Circulation Models At the Organ Levelmentioning
confidence: 99%
“…F I G U R E 2 Computational models for hepatic flow: (a) a 0D model for a rat liver lobe (Debbaut, De Wilde, et al, 2012); (b) a 0D model consists of three pi-filters for modeling the HABR in human liver (Ho, Sorrell, Bartlett, & Hunter, 2013); (c) a hybrid 0D-1D model for simulating flow variations after hepatectomy on pig livers ; (d) a 1D model for a subject-specific portal system (Ho et al, 2011); (e) a 3D model for comparing the streamlines in portal veins between healthy subjects and cirrhotic patients (George et al, 2015) In recent years, 3D computational fluid dynamics simulations have been made for liver radioembolization, which makes use of catheters to deploy radiation-emitting microspheres to desired locations in the hepatic artery network (Aramburu et al, 2019(Aramburu et al, , 2020Bomberna et al, 2022;Taebi et al, 2020). Important parameters such as the size, injection velocity of microspheres, and the location of catheter tip were investigated (Aramburu et al, 2020).…”
mentioning
confidence: 99%
See 1 more Smart Citation